Turnover intention and related factors among resident physicians in China under the standardised residency training programme: a cross-sectional survey. Issue 4 (11th April 2022) - Sun, Xiaoting; Zhang, Mengmeng; Lu, Zhanghong; Zhang, Zhaoyu; Zheng, Jialin Charlie; Cheng, Liming; Zeng, Lianhua; Qian, Yingli; Huang, Lei
Abstract : Objectives: This study aimed at examining the extent of turnover intention among the Chinese resident physicians who entered the newly established national standardised residency training programme (SRTP), and exploring factors associated with their turnover intention. Design: Cross-sectional survey. Setting: Ten institutions from five geographical areas in China. Methods: 1414 residents were surveyed using paper-based questionnaires and scales regarding their demographics, work situation, attitudes towards SRTP, job satisfaction, psychological resilience, burnout and turnover intention in 2017. The turnover intention was described and compared between categorical groups. Linear regressions were used to select the factors associated with turnover intention. The structural equation model was used to capture the potential mediating effects. Results: The mean turnover intention score was 12.45 (SD=4.47). Nearly half (47.87%) of the residents had a high and very high level of turnover intention. Psychological resilience (β=0.066), burnout (β=0.141) and job satisfaction (β=0.022) were positively associated with turnover intention, while specialty (β=−0.135), year of training (β=−0.687), career in medicine (β=−2.191), necessity of training (β=−0.695) and satisfaction with income (β=−1.215) had negative associations with turnover intention. Working hours and nightshift interval indirectly were associated with turnover intention through the mediating effects of burnout. Career in medicine, necessity of training, satisfaction with income, and psychological resilience showed direct effects and indirect effects on turnover intention through burnout and job satisfaction as mediators. Conclusions: The turnover intention among Chinese residents was prevalent and unignorable. Burnout was the major contributing factor, while year of training and positive attitudes towards training were protective factors. Burnout and job satisfaction also served as mediators. Interventions targeting these factors should be incorporated in the training programmes to keep a prosperous physician workforce.